Decentralized Finance (DeFi) and Islamic Economic Law: A Maqāṣid al- Sharīʿah Analysis of Blockchain-Based Financial Ecosystems - Ahmad Ahmad; Muhammad Said; Abdillah Abdillah; Abdulloh Munir; Andi Eki Dwi Wahyuni (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2026)
The emergence of Decentralized Finance (DeFi) represents an innovative shift in modern-day financial systems through which financial services can be delivered between peers using blockchain technology independent of centralized intermediaries. Although the concept of DeFi provides better access, transparency, and efficiency, its adherence to the laws of Islamic economics is a contentious issue among scholars in relation to problems associated with usury (riba), excessive uncertainty (gharar), and gambling (maysir). Adressing, this study seeks to assess the compatibility of DeFi mechanisms with Islamic finance through the lens of maqāṣid al-Shari'ah framework. Using a qualitative library research methodology, the present study discusses classical sources of Islamic jurisprudence, current fatwa, and academic literature related to major DeFi protocols from a maqāṣid perspective. The findings reveal that despite the use of many DeFi platforms with some features do not conform to Sharia principles, the blockchain technology that forms the basis of DeFi systems and the use of smart contracts offer potentials to be used in Sharia-based systems. This study shows that there is potential to reorganize the DeFi protocols based on Islamic principles like murābaḥah, mushārakah, and wakālah and at the same time promoting the main maqāṣid goals, particularly preservation of wealth, faith, and public interest. Furthermore, a conceptual framework that combines Sharia governance with blockchain technology and innovative finance has been suggested.